Key elements of Building Information Modeling (BIM) for BIM-based projects / Wan Nur Syazwani Wan Mohammad ... [et al.] - Wan Mohammad, Wan Nur Syazwani; Abdullah, Mohd Rofdzi; Ismail, Sallehan; Takim, Roshana (2022)
BIM is introduced to support the fourth Industrial Revolution 4.0 (IR4.0) in the construction industry. Through BIM, the construction information is stored, supplied, and received in one single respiratory system which enables the BIM-based project team to interact and collaborate in real-time throughout the project life cycle. Nevertheless, the BIM adoption performance among contractors is relatively low for their projects. One of the reasons is that there is a lack of overarching key elements identified from the previous study of BIM assessment models. The objective of this study is to identify the key elements of BIM used for BIM-based projects adopted from various BIM assessment models. A systematic literature review from various BIM assessment models in the United States, United Kingdom, Netherland, Australia, China, South Korea, and Malaysia was conducted. The findings revealed that four (4) key elements to be considered. These are BIM objectives, BIM uses, BIM adoption components, and project performance criteria. The deliberated key elements cover the assessment of BIM-based projects' performance (i.e., time, cost, quality, and safety) across construction project phases. Hence, the outcomes of this paper could help BIM stakeholders in particular contractors to comprehend various key elements for BIM-based projects in Malaysia.